Utilização de medicamentos por gestantes em atendimento pré-natal no município de Santo Antônio de Jesus - BA - Costa, Débora Bomfim (2015)
The use of medication during pregnancy has been described in pharmacoepidemiological studies. Pregnant women may have health problems that often require the use of drugs, but there are numerous on the consequences to the fetus and to the pregnant woman. To guide the most appropriate therapeutic choice for a pregnant, the US Food and Drug Administration (FDA) classified the medicines according to risk criteria in an attempt to target and make safer the prescription. This work characterizes the Pharmacoepidemiological profile, the factors associated with use of drugs before and during pregnancy and factors associated with use of safe or risk drugs in a population of pregnant women users of the Unified National Health System who were enrolled in prenatal care. A cross-sectional study was conducted with pregnant women in 1091, data were collected from June 2012 to February 2014, through a previously structured form. This form contained questions about socio-economic conditions of the family, demographics, maternal reproductive history, maternal and feeding habits, maternal employment, use of medications and prenatal care. The profile found was a woman with an average age of 25, black, full elementary school and living with a partner. Of respondents 83,0% began their prenatal care in the first trimester and 37.41% had at least four prenatal consultations. The prevalence of drug consumption before and during pregnancy was 52.1% and 84.7% respectively. After analysis, the factors associated with use of drugs before pregnancy were: Pregnant women aged ≥ 30 years old, not black , begin prenatal after the first trimester and be of the economic class C / D / E. There is an increased prevalence of drug use during pregnancy among women with schooling ≥ 11 years of study, have done more than three prenatal visits and have some health problem. The use of risk drugs was observed in 25.2% of pregnant women and the factors associated with such use were: age greater than 24 years, early prenatal care during the first trimester and have some health problem. The results of this study are similar to those described in the literature, where pregnant women are exposed to a wide variety of drugs, and suggest a medicalization of pregnancy and the need to develop scientific evidence able to promote continuous improvement in the quality of maternal and child care, and investments in continuing professional education that promote rational use of medicines in the prenatal period.